2021
DOI: 10.1111/cei.13607
|View full text |Cite
|
Sign up to set email alerts
|

A1 and A2A adenosine receptors play a protective role to reduce prevalence of autoimmunity following tissue damage

Abstract: Adenosine is a potent modulator that has a tremendous effect on the immune system.Adenosine affects T cell activity, and is necessary in maintaining the T helper/regulatory T cell (T reg ) ratio. Adenosine signalling is also involved in activating neutrophils and the formation of neutrophil extracellular traps (NETs), which has been linked to autoimmune disorders. Therefore, adenosine, through its receptors, is extremely important in maintaining homeostasis and involved in the development of autoimmune disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“… 63 A2AR can suppress NETosis in a low‐dose streptozotocin‐induced T1DM model, and plays a protective role in reducing tissue damage. 83 A2AR gene variants have also been shown to be protective against retinopathy in type 1 diabetes. 84 …”
Section: The Role Of A2ar Receptor In Cancers and Autoimmune Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“… 63 A2AR can suppress NETosis in a low‐dose streptozotocin‐induced T1DM model, and plays a protective role in reducing tissue damage. 83 A2AR gene variants have also been shown to be protective against retinopathy in type 1 diabetes. 84 …”
Section: The Role Of A2ar Receptor In Cancers and Autoimmune Diseasesmentioning
confidence: 99%
“…63 A2AR can suppress NETosis in a low-dose streptozotocin-induced T1DM model, and plays a protective role in reducing tissue damage. 83 A2AR gene variants have also been shown to be protective against retinopathy in type 1 diabetes. 84 Multiple sclerosis (MS) is a chronic autoimmune disease involving the central nervous system, and experimental autoimmune encephalomyelitis (EAE) is the most widely used research model of MS. 85 Consistent roles of A2AR appear in the EAE models.…”
Section: A2ar and Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils are also able to produce adenosine by converting released ATP [84,85]. Activation of A1aR promotes chemotaxis, whereas A2A-and A2BaRs suppress neutrophil activation [86]. Especially Sympathetic Nervous System and Mild Chronic Inflammation targeting the A2AaR resulted in decreased IL-8 release by neutrophils [87].…”
Section: Sympathetic Regulation Of Immune Cell Functionsmentioning
confidence: 99%
“…Studies have demonstrated that all four AR subtypes are expressed in neutrophils [25]. In particular, A 1 ARs promote neutrophil chemotaxis, whereas A 2A and A 2B ARs inhibit neutrophil activation [32]. In fact, treatment with the A 2A AR agonist, ATL313, inhibits critical steps in integrin-dependent neutrophil adhesion in vitro and in vivo [33].…”
Section: Rheumatic Diseases and Osteoarthritismentioning
confidence: 99%